How Different Electrolytes Can Influence the Aqueous Solution Behavior of 1-Ethyl-3-Methylimidazolium Chloride: A Volumetric, Viscometric, and Infrared Spectroscopy Approach - Sarmad, Shokat; Zafarani-Moattar, Mohammed Taghi; Nikjoo, Dariush; Mikkola, Jyri-Pekka (Frontiers in Chemistry, 2020)
The density, sound velocity, and viscosity of 1-ethyl-3-methylimidazolium chloride [C2mim]Cl in pure water and aqueous solutions of some electrolytes such as potassium chloride, potassium carbonate, as well as potassium phosphate (weight fraction of salt fixed at ws = 0.11) have been measured over a wide range of temperatures from 298.15 to 318.15 K. The obtained experimental data has been used to compute various volumetric, compressibility, and viscometric parameters, e.g. apparent molar properties, limiting apparent molar and transfer properties. The co-sphere overlap model was employed to describe the dominant intermolecular interactions in the ternary solutions. Additionally, the structure making/breaking nature of the [C2mim]Cl in the ternary solutions has been discussed in terms of Hepler’s constant and the temperature derivative of viscosity B-coefficient (dB⁄dT). The activation free energy of solvent and solute, activation enthalpy, and activation entropy have been calculated by the application of transition state theory. The calculated parameters have been interpreted in the sense of solvent-solute and solute-solute interactions. The Fourier transform infrared (FTIR) studies also have been done for the studied systems. Volumetric, acoustic, viscometric, and spectroscopic studies can render some evidence and help to understand the aqueous solution behavior of ionic liquids.